1995
DOI: 10.1104/pp.107.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of 15-Kilodalton Zein in Novel Protein Bodies in Transgenic Tobacco

Abstract: Zeins, the seed storage proteins of maize, are a group of alcoholsoluble polypeptides of different molecular masses that share a similar amino acid composition but vary i n their sulfur amino acid composition. They are synthesized on the rough endoplasmic reticulum (ER) in the endosperm and are stored in ER-derived protein bodies. Our goal i s to balance the amino acid composition of the methionine-deficient forage legumes by expressing the sulfur amino acid-rich 15-kD zeins in their leaves. However, it is cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 34 publications
7
83
0
1
Order By: Relevance
“…The leaves showed the highest level of accumulation of 8-zein, with stems having the next highest level of accumulation. The seeds had añ 10-fold lower level of 8-zein compared with leaves, as was the case with p-zein in transgenic tobacco (Bagga et al, 1995). Taken together, our results suggest that 8-zein accumulates to significant levels in all of the organs of tobacco plant, as we had reported earlier for p-zein (Bagga et al, 1995).…”
Section: -Zein Accumulates To High Levels In the Vegetative Tissues supporting
confidence: 76%
See 3 more Smart Citations
“…The leaves showed the highest level of accumulation of 8-zein, with stems having the next highest level of accumulation. The seeds had añ 10-fold lower level of 8-zein compared with leaves, as was the case with p-zein in transgenic tobacco (Bagga et al, 1995). Taken together, our results suggest that 8-zein accumulates to significant levels in all of the organs of tobacco plant, as we had reported earlier for p-zein (Bagga et al, 1995).…”
Section: -Zein Accumulates To High Levels In the Vegetative Tissues supporting
confidence: 76%
“…In an earlier study, we showed that p-zein accumulates in ER-derived protein bodies in both tobacco leaves and seeds (Bagga et al, 1995); however, Hoffman et al (1987) reported that p-zein, when expressed in a seed-specific manner in transgenic tobacco, accumulated in vacuolar protein bodies.…”
Section: -Zein and P-zein Can Be Localized In Both Cytoplasmic And Imentioning
confidence: 99%
See 2 more Smart Citations
“…It is thought that direct interactions between zeins are essential for their retention in the ER as properly formed protein bodies (Kim et al, 2002). Experiments using transgenic expression of both a-and g-zeins in heterologous species shed some light on their interaction in protein body formation (Williamson et al, 1988;Bagga et al, 1995Bagga et al, , 1997Coleman et al, 1996). However, interpretation of such studies was limited because they did not take into account endogenous nonzein accessory factors such as Floury1 (Fig.…”
mentioning
confidence: 99%